International and National Legal Trends on The Rights to Gender Transition of Transgender Persons and Practices in Some Asian Countries - Mac Thi Hoai Thuong (Universitas Negeri Surabaya, 2026)
Transgender persons, whose gender identity differs from their assigned sex at birth, face legal-social barriers in gender transition a process tied to identity rights and dignity. This study examines the evolution of international legal instruments and national laws on transgender persons right to gender recognition, highlighting global trends toward progressive protection. The research results confirm that for most countries, the national laws on recognizing the legal gender of transgender persons become more open, simple, accessible, and better ensuring the rights of transgender persons. However, this trend develops unevenly among the countries. Besides the open approach of most countries, certain countries keep very strict regulations on legal gender recognition, and even do not allow gender transition. This comes from some main reasons, such as cultural traditions, legal frameworks, social perspectives, and perceptions on this issue. This research's novelty lies in its synthesis of international trends with Asian practices, identifying pathways for reform. Recommendations urge Asian states to harmonize national laws with international human rights standards, simplifying gender recognition procedures and fostering societal acceptance to better safeguard transgender dignity and equality.